Considerations on antimicrobial prophylaxis in patients with lymphoproliferative diseases: A SEIFEM group position paper. (February 2021) - Busca, Alessandro; Cattaneo, Chiara; De Carolis, Elena; Nadali, Gianpaolo; Offidani, Massimo; Picardi, Marco; Candoni, Anna; Ceresoli, Eleonora; Criscuolo, Marianna; Delia, Mario; Della Pepa, Roberta; Del Principe, Ilaria; et al.
Graphical abstract: Abstract: The therapeutic armamentarium for the treatment of patients with lymphoproliferative diseases has grown considerably over the most recent years, including a large use of new immunotherapeutic agents. As a consequence, the epidemiology of infectious complications in this group of patients is poorly documented, and even more importantly, the potential benefit of antimicrobial prophylaxis remains a matter of debate when considering the harmful effect from the emergence of multidrug resistant pathogens. The present position paper is addressed to all hematologists treating patients affected by lymphoproliferative malignancies with the aim to provide clinicians with a useful tool for the prevention of bacterial, fungal and viral infections.